Landslide dams and their hazard after the 25 April 2015 Gorkha Earthquake in Central Nepal - M.R. Dhital; M.L. Rijal; S.R. Bajracharya (Lowland Technology International, 2016)
Large landslide dams are one of the most destructive natural phenomena. They frequently occur in tectonically active orogenic belts with narrow and steep valleys. Nepal hosts many large landslide dams, some of which must have been caused by past earthquakes. The Mw 7.8 Gorkha Earthquake of 25 April 2015 and its aftershocks triggered off many shallow failures with only a few landslide dams that were either very short-lived or only partially blocked the river course. The area affected by the earthquake belongs to the Lesser Himalayan Sequence, Higher Himalayan Crystallines, and the Tethyan Himalayan Sequence. The severely affected area is made up of such resistant rocks as quartzites, gneisses, granites, marbles, and schists. These rocks have generally three discontinuity sets, which are almost perpendicular to each other. A detailed analysis of dip slopes, anti-dip slopes, and dip-normal slopes in the earthquake-affected area revealed that the dip-normal slopes were the most vulnerable ones. Many rockslides and rock falls began from the crest and created long runout paths. The potential sites of landslide damming can be inferred by analysing morphometric parameters together with seismic, geological, hydro-meteorological, and anthropogenic factors. Such damming sites were identified heuristically at various locations of the major rivers, based on the criteria discussed above. Since the earthquake-triggered failures were concentrated mainly on steep slopes with a high internal relief, a hazard map was prepared by combining the safety factor map with the slope map and the internal relief map. There is a good correspondence between the high hazard zones and the heuristically identified potential sites of landslide damming